Persepsi Orangtua Tentang PAUD dan Motivasi Menyekolahkan Anak ke Lembaga PAUD - Qory Ismawaty (Institut Agama Islam Negeri Madura, 2023)
Early childhood education, abbreviated as PAUD, is coaching focused on children under the age of 6 to master maximum and perfect growth and development. The aim of this research was to find out the perceptions of parents regarding their children's education at an early age and the motivation to send their children to PAUD institutions. The research was conducted from November to January 2022/2023. The study used a qualitative method in which 65 parents who sent their sons and daughters to PAUD institutions in Batam City were respondents who were randomly selected. Research data was collected by means of participant observation, structured interviews and documentation studies. The results of the study showed that parents have different perceptions regarding early childhood education, but overall it can be said that parents' perceptions are quite good. The motivations for parents to enroll their children in PAUD are 1) the ambition of the parents so that the child can quickly read, write and do arithmetic; 2) religious or moral and religious motivation; 3) motivation in exploring and developing children's potential; 4) lighten the task of parents in caring for children at home.